Perancangan Interior Henshin Lounge & Bar di Surabaya - Veronica Veronica; Hedy Constancia Indrani; Poppy Firtatwentyna Nilasari (Intra, 2019)
There is still a lack of a place like the Lounge & Bar in Surabaya to accommodate the activities of young executives to socialize comfortably and pleasantly. Lounge & Bar in Surabaya still lacks a distinctive characteristic and attracts the attention of young people to spend their time there. Lounge & Bar in Surabaya has a design that tends to be the same and unattractive, namely a modern minimalist or vintage style with lots of wood material usage. Therefore, with the "Interior Design of Henshin Lounge & Bar in Surabaya" with the concept of "Dancing Ocean" which is futuristic It is hoped that it will be more attractive for all people to spend time relaxing and socializing in this Lounge & Bar because the design is unique and has never been used by the Lounge & Bar that already exists in Surabaya. Plus this is a well-known branch of Lounge & Bar in Jakarta. The design method used is Design Thinking with stages (1) Discovery (2) Observe (3) Emphatize (4) Ideate (5) Decide (6) Prototype (7) Test (8) Implementation.